2020
DOI: 10.5937/topola2006053p
|View full text |Cite
|
Sign up to set email alerts
|

Predilection of Chaitophorus populeti and Phyllobius oblongus on four clones of white poplar

Abstract: The predilection of Poplar shoot aphid (Chaitophorus populeti Panzer) and European Snout Beetle (Phyllobius oblongus L.) in the first and second growing season in two experimental plantations. Four white poplar clones were tested: Villafranca, L-100, L-80, and L-12. The first experimental plot was established at the beginning of 2019 and the second in 2020 near Novi Sad (northern Serbia). Predilection of C. populeti Panzer was performed on three plants per each of three blocks and every of four clones. Predile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…However, significant differences at hybrid taxa (Table 2) and family level (Supplementary Table S1) exhibited no species contribution to resistance to the poplar moth. Previous studies in eastern Europe have described high variability between P. deltoides clones in resistance toward the poplar moth (Poljaković-Pajnik et al 2005, 2012, but only a few clones of the hybrid P. euroamericana (= P. deltoides × P. nigra) were included in that study. Therefore, the available evidence does not support a significant contribution of P. deltoides to poplar moth resistance in the hybrid poplar taxa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, significant differences at hybrid taxa (Table 2) and family level (Supplementary Table S1) exhibited no species contribution to resistance to the poplar moth. Previous studies in eastern Europe have described high variability between P. deltoides clones in resistance toward the poplar moth (Poljaković-Pajnik et al 2005, 2012, but only a few clones of the hybrid P. euroamericana (= P. deltoides × P. nigra) were included in that study. Therefore, the available evidence does not support a significant contribution of P. deltoides to poplar moth resistance in the hybrid poplar taxa.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of leaf miner pests, there are few reports of poplar resistance although several pests of this group can be relevant (Mattson et al 2001, Charles et al 2014). A few studies in eastern Europe have reported a variable resistance of some P. deltoides clones to L. sinuella (Poljaković-Pajnik et al 2005, 2012), but there is no information about other Populus species, hybrids and clones that might contribute to host-plant resistance for breeding and integrated pest management (IPM) programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the living habits of aphids infesting urban shrubs, and possible negative consequences, it seems necessary to recognize and quantify changes in plant attributes underlying plant vigor and fitness in (often inhospitable) urban environments. The adverse effects on plant growth, metabolism, mineral nutrition, photosynthetic rate, concentration of chlorophyll, and gas exchange parameters [15][16][17][18][19][20][21] have been reported in aphidinfested plants.…”
Section: Introductionmentioning
confidence: 99%
“…It grows well on various site and soil conditions and is somewhat tolerant of climate changes, including drought, temperature, and salinity [ 2 ]. Among the Populus alba L. clones, ‘Villafranca’ is among the most represented and registered reference clones in different nursery trials [ 3 , 4 ]. It is mainly used for the afforestation of river lowlands and is planted in specialised plantations to produce furniture logs, pallets, etc.…”
Section: Introductionmentioning
confidence: 99%